The effect of my sequential and random method associated with real-time feedback in learning to perform some artistic gymnastics skills on the ground movement mat (Journal of the College of Basic Education, 2022)
Motor learning aims to learn mathematical skills through a relatively constant change in the motor behavior of the individual through the use of targeted educational methods and curricula. The mathematical skill, according to the theory of programs, represents a group of nervous instructions that are arranged and coordinated in a way that leads to achieving the goal of a specific motor performance. Through practice and training, these nerve impulses are built and coordinated to reach the level of proficiency, as each skill has its own motor program stored in the motor memory that is summoned and executed by the brain when performing this skill.